117 COVID-19 RCEM research summaries: taking the burden off busy clinicians. Issue 12 (23rd November 2020) - Reynard, Charles; Jafar, Anisa; Oliver, Govind; Darbyshire, Daniel; Prager, Gabrielle; Naguib, Mina; Carley, Simon
Abstract : Aims/Objectives/Background: Entering lockdown on 23rd March 2020 due to the COVID-19 pandemic marked an unprecedented period for healthcare evidence. An exponential increase in published work, pre-prints, guidelines, online information portals and more, has been overwhelming especially when combined with the ever-changing local emergency department responses to COVID-19. Many research projects were either suspended in favour of clinical work or re-routed into pandemic-oriented studies. All the while, the gap between clinical providers and a mountain of information was growing. Our team developed a strategy to deliver the most pertinent evidence to those working in emergency medicine, taking some stress out this aspect of COVID-19 working. Methods/Design: Each week a search was conducted using PubMed of everything produced in the previous 7 days. The number of titles varied from approximately 800 to 2500. A 3 to 5 person team distilled titles and then reviewed abstracts for papers of importance and relevance to emergency medicine. Relevant and high impact journals were individually searched over the same time period. Summaries of the short-listed papers were produced and the weekly editorial team selected 5 for inclusion in the weekly RCEM Top 5 and others were combined for extra reading as part of a 2–3 weekly 'Director's Cut'. Results/Conclusions: The RCEM Top 5 (at time of writing) has been run for 13 weeks. The summaries themselves were accessed by between 3000 and 6000 RCEM members/fellows each week. The work has also fed into online journal clubs and blogs (combined views of over 30, 000) and has attracted interest from wider colleagues nationally and internationally to both join and even replicate the approach to other relevant areas. The positive feedback is best summarised in the following quote: 'when I'm too mentally overcooked to do any reading on my own this helps me feel I am doing some keeping up. Please continue!'